Correlation Between Schizophrenia and Coronavirus Disease in North Sumatera, Indonesia: A Correlative Analytical Study - Amin, Mustafa M.; Futrawan, Richie; Husada, Muhammad Surya (Frontiers in Psychiatry, 2022)
Background In the first quarter of 2020, two cases of coronavirus disease (COVID-19) were reported in Indonesia, approximately 4 months after the first case was reported in China. The numbers continued to increase following the introduction of many variants of the virus. The pandemic may have an impact on the community's mental health, particularly on those with mental illnesses. Therefore, this study aimed to determine the correlation between schizophrenia and COVID-19 based on demographic characteristics. Methods This nominal-nominal and numerical-nominal correlative analytical study used a cross-sectional approach and was conducted at a psychiatric hospital in North Sumatra. The sample population consisted of 48 patients and 48 healthy controls, who were selected using a non-probability consecutive sampling method. Results The analysis showed that there were correlations between schizophrenia and COVID-19 (r = 0.417, p < 0.001) and between the age of patients with schizophrenia and COVID-19 with (r = 0.544). Conclusions COVID-19 is correlated with schizophrenia and the age of patients with schizophrenia. We recommend that patients with schizophrenia follow the same health guidelines as the clinical high-risk group for COVID-19 and receive the same treatment. Physicians that treat patients with COVID-19 should pay close attention to those with schizophrenia because they may underestimate their condition.